EVALUATION OF ACTIVITY OF ALTERNANTHERA SESSILIS LEAVES AQUEOUS EXTRACT ON PLATELET COUNT IN DRUG-INDUCED THROMBOCYTOPENIA IN ALBINO RATS - MR, Nayana; PATIL, DEEPA; AITHAL, SATHISHA; BM, APOORVA (Asian Journal of Pharmaceutical and Clinical Research, 2023)
Objectives of Study: (1) To determine the platelet augmenting effect on drug-induced thrombocytopenia in rats. (2) To observe any adverse effects and mortality in the animals. Methods: Albino rats of either sex of average weight 150–200 g are used. A total of 36 (n=36) rats were divided into VI groups of 6 each. Groups I, II, III received cyclophosphamide 25 mg/kg body weight and group IV, V, VI received 50 mg/kg body weight for 3 consecutive days respectively. Blood was withdrawn from the retro-orbital plexus on the 1st, 4th, 7th, and 11th day of study after subjecting the animals to light anesthesia using ether and platelet count determined by making peripheral smear [8]. Results: Platelet count: Alternanthera sessilis leaves aqueous extract at concentrations of 200 mg/kg and 400 mg/kg were found to significantly increase the platelet count in cyclophosphamide-induced rat model. Conclusion: The present study demonstrated the platelet augmenting effect of A. sessilis leaves aqueous extract. Further detailed studies are required to establish its usefulness.